Reduced reward-driven eating accounts for the impact of a mindfulness-based diet and exercise intervention on weight loss: Data from the SHINE randomized controlled trial. (1st May 2016) - Mason, Ashley E.; Epel, Elissa S.; Aschbacher, Kirstin; Lustig, Robert H.; Acree, Michael; Kristeller, Jean; Cohn, Michael; Dallman, Mary; Moran, Patricia J.; Bacchetti, Peter; Laraia, Barbara; Hecht, Frederick M.; et al.
Abstract: Many individuals with obesity report over eating despite intentions to maintain or lose weight. Two barriers to long-term weight loss are reward-driven eating, which is characterized by a lack of control over eating, a preoccupation with food, and a lack of satiety; and psychological stress. Mindfulness training may address these barriers by promoting awareness of hunger and satiety cues, self-regulatory control, and stress reduction. We examined these two barriers as potential mediators of weight loss in the Supporting Health by Integrating Nutrition and Exercise (SHINE) randomized controlled trial, which compared the effects of a 5.5-month diet and exercise intervention with or without mindfulness training on weight loss among adults with obesity. Intention-to-treat multiple mediation models tested whether post-intervention reward-driven eating and psychological stress mediated the impact of intervention arm on weight loss at 12- and 18-months post-baseline among 194 adults with obesity (BMI: 30–45). Mindfulness (relative to control) participants had significant reductions in reward-driven eating at 6 months (post-intervention), which, in turn, predicted weight loss at 12 months. Post-intervention reward-driven eating mediated 47.1% of the total intervention arm effect on weight loss at 12 months [β = −0.06, SE(β) = 0.03, p = .030, 95% CI (−0.12, −0.01)]. This mediated effect was reduced when predicting weight loss at 18 months ( p = .396), accounting for 23.0% of the total intervention effect, despite similar weight loss at 12 months. Psychological stress did not mediate the effect of intervention arm on weight loss at 12 or 18 months. In conclusion, reducing reward-driven eating, which can be achieved using a diet and exercise intervention that includes mindfulness training, may promote weight loss (clinicaltrials.gov registration:NCT00960414 ).